Sensitive Simultaneous Determination of Rutin and Folic Acid with the Use of a Solid Lead Electrode by Means of Adsorptive Stripping Voltammetry. Issue 11 (11th July 2019) - Ochab, Mateusz; Gęca, Iwona; Korolczuk, Mieczyslaw
Abstract: In this article a solid lead electrode (PbE) was utilized for the first time for determination of organic substances by means of adsorptive stripping voltammetry. A new procedure of simultaneous determination of rutin and folic acid was developed. Two well shaped and well separated reduction signals of rutin and folic acid were obtained with the use of PbE. The optimization of analytical procedure was presented. The calibration graphs for rutin and folic acid for an accumulation time of 120 s were linear in the ranges from 2×10 −9 to 1×10 −7 mol L −1 and from 2×10 −9 to 5×10 −8 mol L −1, respectively. The obtained detection limits for rutin and folic acid determination following accumulation time of 120 s were 7.9×10 −10 and 8.4×10 −10 mol L −1 . Potential interference effects were investigated. The proposed procedure was used for analysis of pharmaceutical preparations with satisfactory results showing practical applications. The analytical parameters of the proposed procedure were compared with other voltammetric procedures of mentioned substances determination. Abstract :